FORMATION OF FOREIGN ECONOMIC STRATEGY OF THE REGION IN TERMS OF RUSSIA'S MEMBERSHIP IN WTO - N. I. Didenko; Dzhamilya Skripnyuk (Модернизация, инновация, развитие, 2015)
Provides an overview of the basic obligations assumed by Russia in connection with the entry into the WTO. The history of Russia's integration with the WTO and the formation of the EurAsEC Customs Union. Assessed the possible impact of Russia's WTO accession on the economy of regions with a view to improving export opportunities and local industry to compete with imports of foreign manufacturers. The mechanism of the formation of the region's foreign economic strategy in the new economy.